2021
DOI: 10.1038/s41598-021-00096-x
|View full text |Cite|
|
Sign up to set email alerts
|

Lactobacillus rhamnosus and Bifidobacterium longum alleviate colitis and cognitive impairment in mice by regulating IFN-γ to IL-10 and TNF-α to IL-10 expression ratios

Abstract: Gut lactobacilli and bifidobacteria on the immune homeostasis. Therefore, to understand the mechanism in vivo, we selected human fecal Lactobacillus rhamnosus NK210 and Bifidobacterium longum NK219, which strongly suppressed the IFN-γ to IL-10 expression (IIE) ratio in lipopolysaccharide-stimulated macrophages. Thereafter, we examined their effects on the endotoxin, antibiotics, or antitumor drug-stimulated immune imbalance in mice. Intraperitoneal injection of lipopolysaccharide and oral gavage of ampicillin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 46 publications
2
12
0
1
Order By: Relevance
“…Probiotics, including Lactobacilli and Bifidobacteria, alleviate gut dysbiosis [ 17 ], immune imbalance [ 18 ], inflammation [ 19 ], depression [ 20 ], and memory impairment [ 21 ]. Bifidobacterium adolescentis IM38 alleviated IS-induced anxiety and high-fat-diet-induced gut inflammation in mice [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics, including Lactobacilli and Bifidobacteria, alleviate gut dysbiosis [ 17 ], immune imbalance [ 18 ], inflammation [ 19 ], depression [ 20 ], and memory impairment [ 21 ]. Bifidobacterium adolescentis IM38 alleviated IS-induced anxiety and high-fat-diet-induced gut inflammation in mice [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Blastocystis ST7 disrupted tight junction proteins such as occludin and ZO-1 [ 48 , 49 ] as well as increases the levels of pro-inflammatory cytokines to trigger an inflammatory response [ 50 , 51 ]. In addition, Lactobacillus rhamnosus and Bifidobacterium longum have shown to alleviate cognitive impairment in mice by regulation the IFN-γ/IL-10 and TNF-α/IL-10 rations [ 52 ], whereas Lactobacillus plantarum and Bifidobacterium longum have also shown to alleviate cognitive impairment in mice by up-regulating NF-kB-mediated BDNF expression [ 43 ]. A recent study has shown that Bifidobacterium breve prevented memory impairment a mouse model with phenotypic features of Alzheimer’s disease through microglia activation and the reduction of amyloid-β production [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…NK209, NK210, and NK219 were cultured in commercial media for probiotics including MRS broth (BD, Franklin Lakes, NJ, USA), centrifuged at 5000× g and at 4 °C for 20 min, and washed with saline [ 23 , 24 ]. The collected cells were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The YMT was performed in a three-arm horizontal maze (40 cm (length), 3 cm (width) and 12 cm (height)) for 8 min, as previously reported [ 19 , 23 ]. The spontaneous alteration (%) was described as a spontaneous to possible alternation ratio.…”
Section: Methodsmentioning
confidence: 99%